Aspekty polityczne i militarne „roku czterech cesarzy” (68-69 r. po Chr.). Część 2: Od śmierci Galby do zwycięstwa Wespazjana - Kozłowski, Jakub; Królczyk, Krzysztof (Studia Europaea Gnesnensia, 2015)
The aim of this paper is to discuss the political and military aspects of the Year of the Four Emperors, i.e. the period of civil war in Rome which began with the death of emperor Nero in June 68, and ended with Vespasian’s ascend to undivided power towards the end of 69. In Part Two, the author discusses the events which took place between the death of the Emperor Galba in January 69 and the final victory of Vespasian’s party in December 69.